ON FACTORIZATION OF A CLASS OF SECOND ORDER MATRIX-FUNCTIONS - Sargsyan, A. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
The paper suggests a factorization construction method for a class of second order matrix-functions. The left lower element of these matrix-functions may be represented as combinations of other three elements of matrix-function and two functions, meromorphic respectively in interior and exterior regions of the unit disk.